Low Bone Turnover Markers in Young and Middle-Aged Male Patients with Type 2 Diabetes Mellitus - X. X. Liu; L. Jiang; Q. Liu; J. Zhang; W. Niu; J. Liu; Q. Zhang (Journal of Diabetes Research)
Accumulating evidence has supported an increased risk of osteoporotic fracture in postmenopausal women and elderly men diagnosed with diabetes mellitus. However, it is not uncommon for young and middle-aged male patients diagnosed with type 2 diabetes mellitus (T2DM) to suffer from osteopenia or osteoporosis. Few studies focused on this population group are available. The aim of this study is to evaluate bone metabolic status and investigate the influence of T2DM on bone metabolism in 30-50-year-old men. Anthropometric assessment and blood samples were obtained from 160 patients with T2DM and 69 nondiabetic volunteers. Serum parathyroid hormone (PTH) and bone turnover markers (BTMs), including serum procollagen type I N-terminal peptide (PINP), osteocalcin (OC), and β-cross-linked C-telopeptide of type I collagen (β-CTX), were analysed. No significant differences were observed based on age, body mass index, systolic blood pressure, serum calcium, phosphorus, creatinine, total protein, and albumin levels when comparing T2DM and control groups. Fasting blood glucose, HbA1c, triglyceride (TG), total cholesterol, and low-density lipoprotein cholesterol were significantly increased, while high-density lipoprotein cholesterol was significantly decreased in the T2DM group. Compared with controls, diabetic patients showed lower serum PINP, OC, and PTH levels, whereas serum β-CTX levels were similar between the two groups. Moreover, HbA1c levels were positively correlated with PINP and inversely associated with PTH levels. TG levels were negatively correlated with OC or β-CTX levels. Furthermore, multiple linear regression revealed a positive correlation between HbA1c and PINP levels. These results also revealed a negative association between HbA1c and PTH, and between TG and OC levels, even after adjusting for expected confounder factors. Collectively, these findings indicated that young and middle-aged male patients with T2DM showed a lower turnover state resulting from bone formation inhibition. Glucose and lipid metabolic disorders may affect bone formation through different pathways.